2021
DOI: 10.1007/s40279-021-01511-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary Periphyseal Stress Injuries in Young Athletes: A Systematic Review

Abstract: Background Overuse injuries are common in sporting children and adolescents. These injuries are a particular concern when they involve the epiphyseal-physeal-metaphyseal (EPM) complex given their potential to disturb skeletal growth. Specifically, the limits of mechanical tolerance of the EPM complex to repetitive stress may be exceeded by the intense and continuous training characteristic of many youth sports today. Objective This article describes the present status of knowledge on the occurrence and outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 152 publications
0
61
0
3
Order By: Relevance
“…It is possible that the high impact of jump training before skeletal maturity may increase the risk of injuries or musculoskeletal conditions. High impact repetitive sport activities in children have been shown to contribute to primary periphyseal stress injuries ( 13 , 14 ). Previous canine biomechanical studies evaluating the effects of jumping on forelimb muscular activation have shown that the jump task is the most physiologically demanding task for all evaluated forelimb muscles ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the high impact of jump training before skeletal maturity may increase the risk of injuries or musculoskeletal conditions. High impact repetitive sport activities in children have been shown to contribute to primary periphyseal stress injuries ( 13 , 14 ). Previous canine biomechanical studies evaluating the effects of jumping on forelimb muscular activation have shown that the jump task is the most physiologically demanding task for all evaluated forelimb muscles ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In general EGPIs are believed to be a consequence of repetitive trauma, in contrast to a single acute event leading to this injury, 34 which places them in the chronic injury group. 7,38 However, in many cases the athletes can describe 1 specific event when they first noticed the injury, suggesting an acute onset on top of a chronic condition. 8,14,34,46 Nevertheless, a single event does not represent a strong-enough trauma to lead to a fracture on its own.…”
Section: Discussionmentioning
confidence: 99%
“…32 While Wen et al 48 described a case of bilateral EGPI as Osgood-Schlatter of the finger, a precise classification, including strain and the various types of fractures, is pending. The definition of these injuries as epiphyseal was recently questioned by Caine et al 7 They proposed the term periphyseal stress injuries since the injury involves 1 or more constituents of the epiphyseal-physeal-metaphyseal complex. [5][6][7] Nevertheless, they also stated that periphyseal strain injuries are not represented within the given classifications and further work on a new classification is pending.…”
Section: Fracture Types and Nomenclaturementioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, an increase in pressure on the posterior horn of the meniscus during occupational activities with deep flexion loading initiates the degenerative process in the joint [ 26 ]. For instance, high-impact sports activities, such as hockey, football, and soccer, lead to undue stress on joints and increase knee OA risk in adults [ 20 , 27 ]. While deep squatting has been shown to increase compressive and posterior shear forces on the knee, 7 and 5 times the body weight, respectively, it is not yet proven that it leads to OA [ 28 ].…”
Section: Pathogenesis and Risk Factorsmentioning
confidence: 99%